From Phone to Finance: Indonesian Female Patterns in Store Payments - Khusniati, Navi'ah; Yusuf, Maulana Ghani (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study investigates the influence of gender and women’s employment status on mobile phone use for in-store financial transactions in Indonesia. Using micro data from the 2021 Global Findex survey and a logistic regression model, this study analyzes the extent to which being a woman, as well as being an employed woman, influences the likelihood of using a mobile phone for in-store transactions. The results show that in general, although not significantly, women are less likely than men to use mobile phones for in-store transactions. However, employed women have a significantly higher probability of using mobile phones for this purpose than unemployed women. These findings demonstrate the importance of women’s participation in the workforce on digital financial behavior in developing countries. Equalizing access to digital literacy and empowering women’s economy are key to driving fairer digital financial inclusion. Robustness tests show that the average marginal effects obtained are consistent. This study contributes to the literature on gender-based digital financial inclusion and provides policy implications for expanding access to mobile financial services more equitably, especially in developing countries.